2018
DOI: 10.1097/mnm.0000000000000889
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the most commonly used (semi-)quantitative parameters of 18F-FDG PET/CT to detect malignant transformation of neurofibromas in neurofibromatosis type 1

Abstract: In patients with neurofibromatosis type 1, transformation of neurofibromas into a malignant peripheral nerve sheath tumor (MPNST) is a severe complication of the disease. Fluorine-18-fluorodeoxyglucose PET/computed tomography (PET/CT) is a viable option for detecting malignant tumors in neurofibromatosis type 1 patients. The aim of this review was to assess the diagnostic performance of the most frequently used parameters of PET/CT in detecting MPNST. An extensive computer search was performed using the Cochra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 112 publications
0
5
0
Order By: Relevance
“…Plexiform variants of MPNSTs carry the highest risk. 3 Hyperparathyroidism in association with NF1 is also a rare occurrence that has been previously described in the literature. Here, we present the case of a patient with neurofibromatosis, primary hyperparathyroidism, and suprarenal MPNST.…”
Section: Malignant Peripheral Nerve Sheath Tumor In a Patient With Neurofibromatosis And Primary Hyperparathyroidismmentioning
confidence: 80%
“…Plexiform variants of MPNSTs carry the highest risk. 3 Hyperparathyroidism in association with NF1 is also a rare occurrence that has been previously described in the literature. Here, we present the case of a patient with neurofibromatosis, primary hyperparathyroidism, and suprarenal MPNST.…”
Section: Malignant Peripheral Nerve Sheath Tumor In a Patient With Neurofibromatosis And Primary Hyperparathyroidismmentioning
confidence: 80%
“…Neurofibromas are the most prevalent benign peripheral nerve sheath tumor classically associated with neurofibromatosis (NF) but also can appear as solitary lesions [1,2]. Those related to NF carry an increased risk of malignant transformation (2-13%), consequently, some cut-off values of SUVmax have been proposed based on a SUVmax greater than 3.2 [3] and lesion-to-liver (T/L) values over 1.5 [4,5,6] but the role of [ 18 F]FDG PET/CT remains still under discussion at this point [7,8]. Complete surgical excision is the treatment of choice in most patients, retaining systemic treatments such as recently FDA-approved selumetinib (tyrosine kinase inhibitor) for diffuse NF cases [9].…”
Section: Clinical Vignettementioning
confidence: 99%
“…However, preoperative identification of malignancy in NF1 patients is particularly difficult, as atypical and plexiform neurofibromas can present similarly to MPNSTs. Recent research has shown that FDG-PET scans can be helpful in distinguishing malignant from benign lesions, differentiating MPNSTs from neurofibromas with an 80% specificity and almost 100% sensitivity [25,26], which is why an NF1 consensus does recommend performing it [22]. Others have shown that diffusion-weighted imaging sequences in MRI can differentiate malignancy with 100% specificity; however these techniques are not standard of care in many centers [24].…”
Section: Preoperative Diagnostics In Mpnst Ideally Mpnstsmentioning
confidence: 99%